Pengaruh Self Efficacy dan Locus Of Control Terhadap Kinerja Karyawan Dengan Kepribadian Sebagai Variabel Moderating (Studi Pada Pt. Wijaya Karya Beton, Tbk Ppb Majalengka) (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2020)
This study aims to determine the effect of self-efficacy and locus of control with personality asa modifying variable on the performance of employees of PT. Wijaya Karya Beton, Tbk PBBMajalengka. The data source in this research is primary data. The study population was allemployees totaling 69 people. The sampling technique uses census techniques, where theentire population is used as a sample. The data collection instrument used a questionnaire.Data analysis techniques using Moderate Regression Analysis (MRA). The results of theanalysis show that partially self-efficacy and locus of control have a positive and significanteffect on employee performance. Likewise, the presence of personality as a moderatingvariable further strengthens the effect of self-efficacy and locus of control on employeeperformance. therefore the company must pay attention to individual beliefs, and expectationsof their ability to achieve the goals of each job will depend on their level of confidence andself-confidence by increasing the capacity of employees through training activities and so on